Advancements in NIR sensing for tuberculosis detection using dilute III-V semiconductors: current status and future prospects - Mamo, Melaku Dereje; Zigyalew, Yaschelewal; Gelan, Seid Emamu; Ntsendwana, Bulelwa; Sikhwivhilu, Lucky (Frontiers in Sensors, 2025)
This mini-review focuses on the use of dilute III-V semiconductors for near-infrared (NIR) sensing and the detection of tuberculosis (TB) in both humans and animals. These composite materials could greatly improve the sensitivity and efficiency of NIR detection. Well, we start off with the effects of TB, old methods of detecting it, and the rise of NIR sensing technologies. The significance of dilute III-V semiconductors for NIR sensing is discussed and the fabrication, properties, and performance of these semiconductors with organic matrices is explored. In this study we test the efficiency of NIR sensors in detecting TB across different species, and discuss the problems and drawbacks that are inherent in the use of these sensors. Lastly, we offer some suggestions for the field of future research and development, stressing the importance of this need for constant innovation. The purpose of this is to hopefully show the possible uses of these hybrid materials, and how they can enhance NIR sensitivity, and open the door to new diagnostic platforms.